A shifting carnivore’s community: habitat modeling suggests increased overlap between the golden jackal and the Eurasian lynx in Europe - Serva, Davide; Iannella, Mattia; Cittadino, Viviana; Biondi, Maurizio (Frontiers in Ecology and Evolution, 2023)
Introduction The European large carnivore community is recently showing positive trends. Beyond those, other species are expanding in Europe. In recent decades, the golden jackal (Canis aureus), a medium-sized canid, has rapidly expanded to western and northern Europe, after being historically confined to the Balkans. The Eurasian lynx (Lynx lynx), an apex predator once widely distributed throughout Europe, was nearly eradicated in the 19th century. Recent reintroductions, legal protection, and its natural expansion brought the lynx to recover, though some populations still face extinction. As the carnivores’ community across Europe is rearranging, ecological interactions are changing as well. Indeed, recent observations reported the golden jackal to kleptoparasitize the lynx. Our research aims to predict the potentially suitable habitats for the golden jackal and the Eurasian lynx, detailing the areas where those are expected to coexist soon. Methods We model their distribution in Europe for current and future scenarios, using both citizen-science and literature data, using the latter to buffer the possible biases of the former. For this aim, we included not only climatic variables, but also several biotic and abiotic predictors relevant to both species. Moreover, given his strong influence on the golden jackal, we compare our results with the predicted distribution of the grey wolf (Canis lupus). Results Our predictions show an increase in habitat suitability for the golden jackal, while an opposite trend is predicted for the Eurasian lynx. Also, we predict the target species to share a large portion of their range in the future, with most of these areas suitable for wolves, too. Discussion Our results may have several impacts in the context of large-scale management, helping to predict further expansion of the golden jackal, and to identify critical areas for lynx conservation, supporting the management of possible reintroductions, also shedding light on the large carnivores’ changing community